Construction of computer-aided industrial design system based on agility. (2015) - Yang, Gangjun; Zhang, Xueliang
Industrial design is one of most creative human activities and it is a process to solve problems of uncertainty. Agile methods of adaptive ideas and human-centred thinking provide references for the solving of industrial design problems. This paper borrowed agile theories from other relevant fields and evolved the principles of agile industrial design-based agility. The first principle is people-oriented design and building a self-organising team. The second is adaptive design and steadily give valuable designs. The third is adopting light-weight design methods or techniques. The final principle includes some practices. Based on the above, computer-aided industrial design system was constructed for building the platform for computer-aided design and design information management. This platform helped to explore design ideas to the utmost. The core modules of the system consisted of three parts - implicit knowledge track of creative thinking, clients involving in design, computer-aided colour design, and design practices templates.